FUNGSIOLEK PADA AKUN INSTAGRAM @RAHASIAGADIS - Dwi Novita Sari; Hasnah Faizah; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to describe the variety of fungsiolek-based functions on @rahasiagadis instagram account. The type of research used is qualitative with a descriptive method. Technique for data collection in this study is referral or observation. Data collected by collecting photographs to be used as materials research, reading and understanding of words or phrases in the photo is repeated, repeated, categorize and cut (crop) photos are obtained with respect to the discussion of the research, the variety fungsiolek-based functions, and include all kinds of functionality on the photo in the accountinstagram @ ramaagagadis. The data collected, analyzed Joss Martin theory by identifying the data, classifying data based on diversity or variety describing data in accordance with the theory study diguakan research and draw conclusions based on the results of the discussion. Based on the results of the research, six hundred photographs are accompanied by words or phrases that are uploaded by @rahasiagadis account, the authors find a hundred photographs are accompanied by words or phrases that contain a variety of fungsiolek. As for the variation or diversity fungsiolek-based functions in @rahasiagadis Instagram account is the language that works for business / trade, health, beauty, knowledge, sports, friendship, romance, song, literature, relaxed and intimate. The dominant variation or variety of eleven data found is a language that works for health. The least variation is the company / trade.Keywords: variety of functions, instagram.